Ginkgetin inhibits the growth of DU−145 prostate cancer cells through inhibition of signal transducer and activator of transcription 3 activity. Issue 4 (20th February 2015) - Jeon, Yoon Jung; Jung, Seung‐Nam; Yun, Jieun; Lee, Chang Woo; Choi, Jiyeon; Lee, Yu‐Jin; Han, Dong Cho; Kwon, Byoung‐Mog
Abstract : Signal transducer and activator of transcription 3 (STAT3) is constitutively activated in human cancers. Therefore, STAT3 is a therapeutic target of cancer drug discovery. We previously reported that natural products inhibited constitutively activated STAT3 in human prostate tumor cells. We used a dual‐luciferase assay to screen 200 natural products isolated from herbal medicines and we identified ginkgetin obtained from the leaves of Ginkgo biloba L. as a STAT3 inhibitor. Ginkgetin inhibited both inducible and constitutively activated STAT3 and blocked the nuclear translocation of p‐STAT3 in DU‐145 prostate cancer cells. Furthermore, ginkgetin selectively inhibited the growth of prostate tumor cells stimulated with activated STAT3. Ginkgetin induced STAT3 dephosphorylation at Try705 and inhibited its localization to the nucleus, leading to the inhibition of expression of STAT3 target genes such as cell survival‐related genes ( cyclin D1 and survivin ) and anti‐apoptotic proteins (Bcl‐2 and Bcl‐xL). Therefore, ginkgetin inhibited the growth of STAT3‐activated tumor cells. We also found that ginkgetin inhibited tumor growth in xenografted nude mice and downregulated p‐STAT3 Tyr705 and survivin in tumor tissues. This is the first report that ginkgetin exerts antitumor activity by inhibiting STAT3. Therefore, ginkgetin is a good STAT3 inhibitor and may be a useful lead molecule for development of a therapeutic STAT3 inhibitor. Abstract : Ginkgetin, isolated from Ginkgo biloba, is highly effective in prostate cancer cells with activated‐STAT3. Ginkgetin has low toxicity against normal human cells and selective toxicity toward cancer cells. Ginkgetin suppressed DU‐145 tumor growth and STAT3 activities in the tumor tissues grown from DU‐145 cells in an animal model.